2003
DOI: 10.1002/pros.10298
|View full text |Cite
|
Sign up to set email alerts
|

Difference of cancer core distribution between first and repeat biopsy: In patients diagnosed by extensive transperineal ultrasound guided template prostate biopsy

Abstract: These results suggest that transrectal sextant biopsies miss more cancers in the anterior region than in the posterior. We believe template technique has an advantage to be able to detect cancer equally in the anterior and posterior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 20 publications
5
37
0
3
Order By: Relevance
“…Furuno et al 4 report using transperineal template-guided approach in the initial biopsy setting and achieved a 49% cancer detection rate using an average of only 18 cores. In this same study, the group reported a 26% yield in the repeat biopsy setting, with an average of 19 cores sampled.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furuno et al 4 report using transperineal template-guided approach in the initial biopsy setting and achieved a 49% cancer detection rate using an average of only 18 cores. In this same study, the group reported a 26% yield in the repeat biopsy setting, with an average of 19 cores sampled.…”
Section: Discussionmentioning
confidence: 99%
“…TTMB was originally used at our institution only for men who had undergone at least one prior negative biopsy, but had persistently elevated prostate specific antigen (PSA) and/or a diagnosis of atypical small acinar proliferation or multifocal high-grade prostatic intraepithelial neoplasia on prior biopsy. Eventually, as other institutions began publishing on use of the transperineal approach for initial biopsy, 4,5 we began to offer TTMB to men as initial biopsy procedure for an elevated PSA. This study reports on 294 men who underwent TTMB as repeat biopsy and 79 men who had TTMB performed as initial biopsy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have adapted the template grid technique for prostate biopsy to detect early-stage prostate carcinoma in men who have not undergone a previous biopsy, as well as those who had previous negative biopsies and remained at high risk for prostate carcinoma. 8 In the current study, we analyzed the distribution of carcinoma cores in the prostate with systematic ultrasound-guided transperineal template biopsy to demonstrate whether prostate carcinoma is distributed equally throughout the entire prostate.…”
mentioning
confidence: 99%
“…Furuno et al demonstrated that on repeat biopsy in high risk patients, the anterior region of the prostate harbors cancers which cannot be detected with standard biopsy techniques. 5 Increasing the number of cores for larger prostates allows us to find prostate cancer foci that may be missed with standard techniques. Remzi et al developed a nomogram that incorporates prostate size and patient age to maximize the detection of prostate carcinoma in the prostate specific antigen (PSA) range of 2 to 10 ng/ml.…”
mentioning
confidence: 99%